PENATALAKSANAAN STROKE TROMBOTIK: PELUANG PENINGKATAN PROGNOSIS PASIEN - Nurul Arofah, Annisa (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2011)
Stroke is a disease that needs multidisciplinary approach and the incident is still increasing. Primary precaution, secondary precaution and tertiary precaution are needed to reduce the incident of stroke and number of impairment. Many progress of the studies about treatments for ischemic thrombotic stroke are hold great promise for the better outcome. Thrombolytic therapy is has a main role in the acute phase treatment for the vascular target but the window therapy is narrow. There is important to overcome strategies to enhance the efficacy of thrombolytic therapy. Besides, neuroprotective agents are also important to decrease the number of disability because they are used to protect the ischemic neuron from the irreversible injury. In animal models of stroke neuroprotective agents are also hold great promise but investigators are still searching for a safe and effective agent that can limit ischemic damage in human stroke. Clinical trials are still needed to improve a better guideline of ischemic thrombotic stroke. Keyword: stroke, thrombotic, guideline.